Isolated bilateral optic neuritis revealing a Lyme Disease : case report: Isolated bilateral optic neuritis revealing a Lyme Disease : case report - LOUIS DE GONZAGUE, MIRAY (Advances in Social Sciences Research Journal, 2020)
Optic neuritis (ON) is an inflammation of the optic nerve and one of the most common manifestations of central nervous system involvement caused by various etiologies. Lyme optic neuritis is a rare ocular manifestation of Lyme Disease. We report a case of a 13-year-old male patient, previously healthy, with decreased central visual acuity on his both eyes . On examination, best-corrected visual acuity on both eyes was 0,3 LogMar. Anterior segment biomicroscopy showed no inflammatory signs and the intraocular pressure was normal. A fundus examination performed under mydriasis revealed a swollen optic disk on both eyes confirmed by fluorescein angiography. The cerebrospinal fluid examination and Lyme Disease blood findings were positive. The diagnosis of Lyme disease-related optic neuritis was made. Treated with Ceftriaxone and Doxicycline, there was a vision recovery. We can state that isolated bilateral optic neuritis is uncommon and exceptional especially in children during Lyme disease.